Pulsed field ablation for atrial fibrillation: acute procedural efficacy and safety of an initial German multicenter experience. (3rd October 2022) - Gunawardene, M A; Lemoine, M; Deneke, T; Wakili, R; Steven, D; Schaeffer, B; Rillig, A; Nentwich, K; Siebermair, J; Filipovic, K; Simu, G; Riesinger, L; et al.
Abstract: Background: Pulsed field ablation (PFA) is a novel non-thermal energy source to conduct catheter ablation of atrial fibrillation (AF). However, real-world multi-center data regarding acute procedural efficacy and safety is sparse. Purpose: To study acute procedural success and safety in patients undergoing PFA for catheter ablation of AF in a multicenter registry. Methods: Consecutive paroxysmal and persistent AF patients undergoing PFA-based catheter ablation using a multispline catheter were enrolled. The cohort included first and repeat ablation procedures. Procedural parameters, acute success and in-hospital safety were evaluated. A follow-up of all patients was conducted. Results: Five German centers enrolled a total of 154 patients undergoing PFA in this study. Mean age was 68±12 years, median CHA2DS2-VASc Score was 3 (Q1-Q3: 2–4). Patients suffered from paroxysmal AF (n=55; 36%), persistent AF (n=93; 60%) and consecutive atrial tachycardias (AT) due to previous CA (n=6; 4%). The median left atrial (LA) PFA and total procedure times were 33 (Q1-Q3: 24–53) and 90 (Q1-Q3: 73–116) minutes, respectively. Mean LA PFA fluoroscopy and total fluoroscopy times were 12.1±5.5 and 20.2±8.7 minutes. Of all 154 procedures, 130 (84%) were index ablation procedures with isolation of pulmonary veins (PVI) only and 24 (16%) were repeat procedures (including re-PVI and ablation of consecutive AT). Acute PV reconnection following primary PVI and the initial set of PFA-applications was found in 20/130 (15%) patients, necessitating additional PFA ablation. Finally, successful PFA-guided PVI was achieved in all patients. Additional PFA lesion sets (including LA posterior wall isolation, anterior ablation, mitral isthmus ablation) were applied in 17/154 (11%) patients. Complications occurred in a total of 6/154 (3.8%) patients (including three groin site complications, two pericardial tamponades, one transient coronary spasm without sequela). The follow up data is still being assessed and will be provided by the time of the ESC 2022 meeting. Conclusion: PFA performed in patients with atrial fibrillation demonstrates high acute procedural success rates and a favorable safety profile in this first real-world multicenter registry. Funding Acknowledgement: Type of funding sources: None.